Concurrent infections of Giardia duodenalis, Enterocytozoon bieneusi, and Clostridium difficile in children during a cryptosporidiosis outbreak in a pediatric hospital in China. - Lin Wang; Lihua Xiao; Liping Duan; Jianbin Ye; Yaqiong Guo; Meijin Guo; Lili Liu; Yaoyu Feng (Public Library of Science (PLoS), 2013)
BACKGROUND: Over 200 cryptosporidiosis outbreaks have been reported, but little is known if other enteric pathogens were also involved in some of these outbreaks. Recently, an outbreak of cryptosporidiosis linked to poor hygiene by two Cryptosporidium hominis subtypes occurred in a pediatric hospital ward (Ward A) in China, lasting for more than 14 months. In this study, the concurrence during the outbreak of three other enteric pathogens with a similar transmission route, Giardia duodenalis, Enterocytozoon bieneusi, and Clostridium difficile, was assessed. METHODS/PRINCIPAL FINDINGS: The occurrence of G. duodenalis, E. bieneusi, and C. difficile in 78 inpatients from Ward A and 283 and 216 inpatients from two control wards (Wards C and D) in the same hospital was examined using molecular diagnostic tools. Significantly higher infection rates were found in children in Ward A for all study pathogens than in Wards C and D (P<0.01): 9.5% versus 1.4% and 0% for G. duodenalis, 10.8% versus 2.8% and 3.7% for E. bieneusi, and 60.8% versus 37.8% and 27.8% for C. difficile, respectively. These differences were mostly seen in children ≤ 12 months. Enteric pathogen-positive children in Ward A (31/58 or 53.4%) were more likely to have mixed infections than those in Ward C (4/119 or 3.4%) or D (5/68, 7.4%; P<0.01). Having cryptosporidiosis was a risk factor for G. duodenalis (OR = 4.3; P = 0.08), E. bieneusi (OR = 3.1; P = 0.04), and C. difficile (OR = 4.7; P<0.01) infection. In addition, a lower diversity of G. duodenalis, E. bieneusi, and C. difficile genotypes/subtypes was observed in Ward A. CONCLUSIONS/SIGNIFICANCE: Data from this study suggest that multiple pathogens were concurrently present during the previous cryptosporidiosis outbreak. Examination of multiple enteric pathogens should be conducted when poor hygiene is the likely cause of outbreaks of diarrhea.